A8.6 A novel therapeutic approach in systemic rheumatic autoimmune disorders: encapsulated human umbilical cord wharton jelly-derived mesenchymal stem cells. (13th February 2015) - Alunno, A; Montanucci, P; Bistoni, O; Basta, G; Caterbi, S; Pescara, T; Pennoni, I; Bartoloni, E; Calafiore, R; Gerli, R
Abstract : Background and objectives: hUCMS are adult stem cells able to exert immune-modulatory either via cell-cell contact or by the secretion of soluble mediators including indoleamine 2–3 dioxygenase (IDO) and HLA-G. We recently developed an endotoxin-free alginate matrix which can be used to microencapsulate (CpS) different cell types and grafted into a non-immunosuppressed host. We previously performed a phase I trial grafting encapsulated pancreatic islets in patients with type 1 diabetes (T1D). To date, data concerning therapeutic application of hUCMS in systemic and organ-specific autoimmune disorders are rather scarce and controversial. In addition, grafting procedures of free hUCMS are limited by safety issues. In this study we aimed to assess the in vitro immune-modulatory effects of CpS-hUCMS on T cells isolated from patients with systemic lupus erythematosus (SLE) and Sjögren's syndrome (pSS). Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from SLE and pSS patients and from healthy donors (HD) to establish co-cultures with CpS-hUCMS at different ratios. Lymphocyte proliferation and phenotypic analysis before and after culture was performed by flow cytometry and real-time PCR. Phenotypic analysis of hUCMS was performed by real time PCR and western blotting. Results: CpS-hUCMS were able to inhibit pSS and HD PBMC cell proliferation but not SLE PBMC cell proliferation. Of interest, in pSS and HD such inhibition was even more evident by progressively reducing hUCMS in culture. In pSS CpS-hUCMS inhibited Th1 and Th17 arm of effector T cells as well as potentiated the T regulatory cell counterpart. The evaluation of soluble molecules produced by hUCMS in such a system revealed a peculiar milieu responsible for the phenotypic and functional effects exerted on pSS PBMCs. Additional studies to understand the lack of efficacy in SLE and design different in vitro systems are currently ongoing. Conclusion: Since CpS-hUCMS appear to rebalance Treg/Th17 ratio in pSS, this may suggest possible therapeutic effects by using this technology in vivo .